Healing Breaths and Rotting Bones: on the Relationship Between Buddhist and Chinese Meditation Practices During the Eastern Han and Three Kingdoms Period - Greene, Eric Matthew (Journal of Chinese religions, 2014)
This article examines the presentation and interpretation of Buddhist meditation in China during the Han and Three Kingdoms period. Previous scholarship has often claimed that during this period of time the Chinese were most attracted to those Indian Buddhist meditation practices that were seen, or had the potential to be seen, as similar to native Chinese breathing exercises, and that Buddhist meditation was accordingly interpreted through the lens of such practices. Through an examination of the key early Chinese Buddhist sources pertaining to meditation, including newly discovered texts found at Kongo-ji temple in Japan, I argue that this long-standing interpretation of how Buddhist meditation came to be accepted in China is not correct. Buddhist meditation practices were, rather, self-consciously presented as the polar opposite of native Chinese meditation practices, and methods such as the contemplation of bodily impurity, seen by previous scholars as unappealing to the early Chinese audience, were in fact highly valued.